Strategi Pengembangan Wisata Gua Pindul Melalui Program Pemberdayaan Masyarakat Sekitar (Studi Kasus Pada Obyek Wisata Gua Pindul) - Erlangga Brahmanto (Universitas Bina Sarana Informatika, 2013)
There is no doubt that Tourism is one of the sectors producing foreign exchange for our country. The utilization, processing, financing of tourism objects have to get serious attention from local governments, stakeholders and citizens of the surrounding attractions. It must be noted that things had become the icon of the area and able to compete with other attractions or a type. In the development of tourism, Management is certainly alot of problems – problems that arise over his running time. This is due to less maximum processing, development of tourism without involving or even empower communities around things. The intervention of the Government District is also deemed less. Keywords: Tourism, Tourism Strategies, Tourism Management, Human resources